THE PROBLEM OF GRANITE GENESIS IN EARLY PROTEROZOIC RIFTOGENIC BELTS WITH REFERENCE TO THE SOUTHERN PECHENGA ZONE, KOLA PENINSULA - Skuf'in P.K.; Bayanova T.B.; Smolkin V.F.; Apanasevich E.A.; Levkovich N.V. (My University, 2003)
One of the key problems in reconstructing the geodynamic environments of the Pechenga-Varzuga belt is the timing and genesis of granitoids widespread along the southern border of the belt, mostly in the southwestern framing of the Pechenga structure. The largest of the numerous dome-shaped granite massifs are the Kaskeljavr and the Shuonijavr massifs. Geophysical evidence suggests that the massifs are rootless domes, whose lower boundary is located at depths of approximately 3 km. The massifs consist of granodiorites and quartz diorites (phase I) and plagiogranites (phase II). The plagiogranites were dated by the U-Pb method with the use of accessory zircon and titanite. The titanite and zircon were subdivided into two types (of magmatic and metamorphic genesis), which differ in morphology, color, and composition. The metamorphic zircon is strongly discordant, and the isochron defined by this mineral yields an age of 1735 ± 24 Ma at MSWD = 0.28. This age corresponds to the late Karelian stage or Svecofennian metamorphism, which is widespread in the Pechenga structure itself and its basement. The isochron defined by the magmatic zircon and titanite has an upper intercept at 1939 ± 7 Ma at MSWD = 0.2, which is interpreted as the timing of the origin of the Shuonijavr plagiogranite. Our data indicate that the granitoids of the Southern Pechenga Zone were formed a little bit later (by 40 Ma) than the thick ferropicrite-basalt piles and intrusions of Ni-bearing gabbro-wehrlites in the Northern Pechenga Zone, which mark the stage of the maximum extension of the paleorift.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой